Faith, Language, and Technology: Developing a Multimodal ESP Textbook for Islamic Education - Syafitri, Widya; Dewi, Merry Prima; Putri, Hilma Pami; Putri, Nayara Syafrianti (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2026)
English textbooks in Islamic higher education often lack contextual relevance and multimodal features essential for English for Specific Purposes (ESP) instruction. This study developed and evaluated a multimodal ESP textbook integrating Islamic values and digital literacy, in alignment with the institutional vision of UIN Sjech M. Djamil Djambek Bukittinggi. An R&D design was employed. Practicality was assessed via a validated questionnaire (Cronbach's α = 0.87); effectiveness was measured through pre- and post-test scores analyzed using an independent samples t-test. Seventy-six students were assigned to an experimental group (n = 40) using the self-developed textbook and a control group (n = 36) using conventional materials across six weeks (100 min each). Pre-test results confirmed baseline equivalence (p > 0.05). The textbook achieved a high practicality rating (M = 4.25; 85.09%). Post-test scores showed a significant group difference (t = 7.496, p < 0.05), with the experimental group outperforming the control group (M = 77.93 vs. 56.06). Effect size was large (Cohen's d = 1.96). The self-developed multimodal ESP textbook is both practical and effective for Islamic Education study program students. Findings support faith-integrated multimodal design as a worthwhile approach for ESP curriculum development in Islamic higher education. Future research should explore long-term retention and cross-institutional replication.